Effects of two packaging materials and storage conditions on the quality of fresh taste, a natural and locally produced orange drink in Ghana - Anin, S.K.; Ellis, W.O.; Adubofuor, d J. (Global Journal of Food and Agribusiness Management, 2011)
Fresh Taste is a natural orange drink product produced in Ghana and packaged in high density polyethylene (HDPE) plastic sachets. The packaging material (sachet) used has been found to be ineffectively designed, particularly its aesthetic appeal and seal integrity. The study was thus conducted to assess the protective function of the alternative package (HDPE bottle) and the existing package (HDPE sachet) on some quality attributes of the product. Samples of the product were stored under refrigeration, room and outdoor conditions over a 7-week period. Microbial load (Yeast and Coliform), titratable Acidity (TTA %) and organoleptic perceptions of sensory panellists served as the measurable indicators for the protective function of the packages. A comparative study was also conducted on the effectiveness of the communication function of the two packaging materials. The results showed that, there was no significant difference between the effectiveness of the protection provided by the High Density Polyethylene bottle and the High Density Polyethylene sachet at 95% confidence level. A significant difference was observed between the communicative function of the bottle packaged product and the existing sachet-packaged Fresh Taste product. The overall rating of panellist for the sachet and labelled bottle however were satisfactory and very good respectively. More than half of the panelists (52%) indicated the illegibility of the displayed details on the HDPE sachet as the major deficiency